Emlékezet-gesztusok a zilahi református kollégium könyvtára körül - Farmati, Anna (Per Aspera ad Astra, 2018)
The study starts from a possessor’s note found in a volume by Calvin in 1816 by the old preacher Nagy Péter who has donated this 16th century book to the school library. This symbolic gesture will be used as guide in a process of establishment of a particular memory-construction. Through the presentation of school’s and library’s history, and mainly through the interpretation of the catalogue of this 16th-century Latin books is built up an interpretation which specifies this library not as a memory place, but rather as a science place (Christian Jacob’s term) in the context of his current use and cultural assessment. Photo: Zilahi Református Wesselényi Kollégium